A Região Nordeste nos livros didáticos de geografia: uma análise histórica - Lopes, Lucineide Fábia Rodrigues (2009)
The objective of this study is to investigate the relationship between school knowledge and academic knowledge. Everyday work and the way the findings and revisions of scientific subjects are published, mainly the Press and cultural industry, almost always associate the academic production to the contents to be taught at school leading thus, to a hierarchical vision. This work follows as a theoretical approach the history of the school subjects since it advocates a hierarchical relationship between school knowledge and academic knowledge. It also assumes school as a place of production of scholastic achievements. In order to attain our goal the following books were analised GEOGRAPHIA DO BRASIL (1927) by Delgado de Carvalho, GEOGRAFIA DO BRASIL ( 1958) by Aroldo de Azevedo e GEOGRAFIA CRÍTICA, O ESPAÇO SOCIAL E O ESPAÇO BRASILEIRO (2006) by José William Vesentini e Vânia Vlach, whose approach is the history of school subjects. Seen from this perspective, we try to understand the way the content North-east region is presented in the referred works. It is understandable that the didactic book is not by itself responsible for schooling, whose relationship depends upon a series of complex factors, however, its discussion follow the school educational practices. As such, we worked these didactic resources so as to understand their contribution for the history of Geography as school subject. A dialogue with various authors about region as geographical category is presented in order to systematize how it was constituted in the field of Geography. In this work the fundamental aspect is to analyze how region is treated in Geography at school and how this relation is connected. By analyzing the referred didactic books we intend to contribute to the history of thinking and educational practices and experiences. Thus, we believe that revealing contents of representations and predominant values in a certain period of a society allow us discuss anew intentions and projects of construction and social formation. The didactic book and formal education are not out of political and cultural contexts as well as domineering relations being, many times, useful instruments for legitimizing systems of power. Due to the fact that they are representative of specific cultural universe, they play, actually, the role of mediators between concepts and political and cultural practices turning themselves important parts in the mechanism of maintenance of determined views of the world.